Anticancer activity, phytochemical investigation and molecular docking insights of Citrullus colocynthis (L.) fruits - Yasmine M. Mandour; Esraa Refaat; Heba D. Hassanein (Scientific Reports, 2023)
Abstract Cancer disease is regarded as one of the most significant public health issues, regardless of economic standards. Medicinal plants are now regarded as a natural source of anticancer medicines due to their antioxidant and anti-mutagenic actions. Cucurbitaceae is considered to be one of the most economically significant families. One family species is Citrullus colocynthis (L.), which has a high concentration of many active secondary chemical metabolites. Various C. colocynthis plant extracts showed cytotoxicity against some cancer cells. This study aims to identify the C. colocynthis fruit components and determine whether they have anticancer action against MIA PaCa-2 and A431 cells. High-Performance Liquid Chromatography/Quadrupole Time of Flight/Mass Spectrometry (HPLC/QTOF/MS); the technique was accustomed to investigate the compounds of the ethyl acetate (EtOAc) fruit extract. Anticancer activity was investigated on both MIAPaCa-2 and A-431 cell lines. DPPH assay for antioxidant activity was carried out. Molecular modelling was employed to help understand the molecular basis for the observed anticancer activity. 24 compounds were tentatively identified by comparing the extract’s fragmentation pattern in positive mode against reference compounds spectra and literature. The EtOAc extract of C. colocynthis had effective positive results on cancer cells (MIAPaCa-2 and A-431) and was characterized by slight or no harmful effect on normal (healthy) cells. For the DPPH assay, EtOAc and BuOH extracts exhibited high antioxidant activity (86 and 76%, respectively) compared with the oxidative potential of the standard compound (Caffeic acid, 98%). One of the major cucurbitacin derivatives that LC/MS tentatively identified in the EtOAc extract was Cucurbita-5(10),6,23-triene-3β,25-diol. During this study, docking experiments and MD simulations were carried out, which suggested the anti-pancreatic cancer activity of C. colocynthis extract to be attributed to EGFR inhibition by Cucurbita-5(10),6,23-triene-3β,25-diol. Therefore, expansion of this type of research should be encouraged in the hope of obtaining natural therapeutics for cancerous tumors in the future, having the advantage of being cheaper, safer, and with fewer side effects.